Mapping the magnetic transition temperatures for medium- and high-entropy alloys - Huang, Shuo; Holmström, Erik; Eriksson, Olle; Vitos, Levente (Intermetallics, 2018)
Tailorable magnetic state near room temperature is very promising for several technological, including magnetocaloric applications. Here using first-principle alloy theory, we determine the Curie temperature (TC) of a number of equiatomic medium- and high-entropy alloys with solid solution phases. All calculations are performed at the computed lattice parameters, which are in line with the available experimental data. Theory predicts a large crystal structure dependence of TC, which explains the experimental observations under specified conditions. The sensitivity of the magnetic state to the crystal lattice is reflected by the magnetic exchange interactions entering the Heisenberg Hamiltonian. The analysis of the effect of composition on TC allows researchers to explore chemistry-dependent trends and design new multi-component alloys with pre-assigned magnetic properties. [Display omitted] •The magnetic state of equiatomic HEAs depends sensitively on alloy components.•In general, early transition metals (e.g., Cr) decrease and noble metals (e.g., Pt) increase the TC of equiatomic fcc HEAs.•The magnetic order survives up to 400–500 K larger temperatures in the bcc phase than in the fcc phase.•For most of the HEAs, the ferromagnetic exchange interactions are more dominating in the bcc phase than in the fcc phase.